RhoA promotes osteoclastogenesis and regulates bone remodeling through mTOR-NFATc1 signaling - Jirong Wang; Chengyun Xu; Jing Zhang; Yizhong Bao; Ying Tang; Xiaoling Lv; Bo Ma; Ximei Wu; Genxiang Mao (BMC, 2023)
Abstract Background The cytoskeletal architecture of osteoclasts (OCs) and bone resorption activity must be appropriately controlled for proper bone remodeling, which is associated with osteoporosis. The RhoA protein of GTPase plays a regulatory role in cytoskeletal components and contributes to osteoclast adhesion, podosome positioning, and differentiation. Although osteoclast investigations have traditionally been performed by in vitro analysis, however, the results have been inconsistent, and the significance of RhoA in bone physiology and pathology is still unknown. Methods We generated RhoA knockout mice by specifically deleting RhoA in the osteoclast lineage to understand more about RhoA's involvement in bone remodeling. The function of RhoA in osteoclast differentiation and bone resorption and the mechanisms were assessed using bone marrow macrophages (BMMs) in vitro. The ovariectomized (OVX) mouse model was adopted to examine the pathological effect of RhoA in bone loss. Results Conditional deletion of RhoA in the osteoclast lineage causes a severe osteopetrosis phenotype, which is attributable to a bone resorption suppression. Further mechanistic studies suggest that RhoA deficiency suppresses Akt-mTOR-NFATc1 signaling during osteoclast differentiation. Additionally, RhoA activation is consistently related to the significant enhancement the osteoclast activity, which culminates in the development of an osteoporotic bone phenotype. Furthermore, in mice, the absence of RhoA in osteoclast precursors prevented occurring OVX-induced bone loss. Conclusion RhoA promoted osteoclast development via the Akt-mTOR-NFATc1 signaling pathway, resulting a osteoporosis phenotype, and that manipulating RhoA activity might be a therapeutic strategy for osteoporotic bone loss.